Chronic Lung Allograft Dysfunction: Evolving Concepts and Therapies - DerHovanessian, Ariss; Wallace, W. Dean; Lynch, Joseph P., III; Belperio, John A.; Weigt, S. Sam (Seminars in Respiratory and Critical Care Medicine, 2018)
Lung transplantation has become an established therapeutic option for a variety of end-stage lung diseases. Technical advances in graft procurement, implantation, perioperative care, immunosuppression, and posttransplant medical management have led to significant improvements in 1-year survival, but outcomes after the first year have improved minimally over the last two decades. The main limitation to better long-term survival after lung transplantation is chronic lung allograft dysfunction (CLAD). CLAD also impairs quality of life and increases the costs of medical care. Our understanding of CLAD manifestations, risk factors, and mechanisms is rapidly evolving. Recognition of different CLAD phenotypes (e.g., bronchiolitis obliterans syndrome and restrictive allograft syndrome) and the unique pathogenic mechanisms will be important for developing novel therapies. In addition to alloimmune-mediated rejection, we now recognize the importance of alloimmune-independent mechanisms of injury to the allograft. CLAD is the consequence of dysregulated repair of allograft injury. Unfortunately, currently available therapies for CLAD are usually not effective. However, the advances in knowledge, reviewed in this manuscript, should lead to novel strategies for CLAD prevention and treatment, as well as improvement in long-term outcomes after lung transplantation. We provide an overview of the evolving terminology related to CLAD, its varying clinical phenotypes and their diagnosis, natural history, pathogenesis, and potential treatments.
Keywords: lung transplantation; chronic rejection; chronic lung allograft dysfunction; bronchiolitis obliterans syndrome; restrictive allograft syndrome